FACTORS RELATED TO KNOWLEDGE OF EARLY MOBILIZATION AMONG POST SECTIO CAESAREA MOTHERS AT RSUD ISKANDAR MUDA IN 2024 - Tamba, Anggun Evany; Zuliani, Cut; Putri Bakara, Sri Muliana; Sipayung, Grace Daniella; Putri, Nabila Rara (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
This study aimed to determine the factors associated with the knowledge of post-cesarean section mothers regarding early mobilization at Iskandar Muda Regional General Hospital in 2024. Early mobilization is an essential component of postpartum care following cesarean section, as it helps accelerate recovery, improve blood circulation, reduce the risk of postoperative complications, and support the restoration of normal body functions. This research employed a descriptive cross-sectional design. The population and sample consisted of all post-cesarean section mothers treated at Iskandar Muda Regional General Hospital in 2024. Samples were selected using an accidental sampling technique. Data were collected through structured questionnaires and analyzed using univariate and bivariate statistical methods. The Chi-Square test was used to determine the relationship between independent variables and the level of maternal knowledge regarding early mobilization. The findings revealed that age, educational level, and access to information were significantly associated with mothers’ knowledge of early mobilization. Mothers with higher educational backgrounds, greater access to health information, and mature age groups tended to demonstrate better knowledge compared to others. Adequate knowledge regarding early mobilization can encourage mothers to perform movement activities earlier, thereby enhancing the recovery process, preventing complications such as thrombosis and delayed wound healing, and improving overall postpartum outcomes. In conclusion, age, education, and information are important factors influencing the knowledge of post-cesarean section mothers regarding early mobilization. Strengthening health education and providing comprehensive information by healthcare professionals are recommended to improve maternal knowledge and promote the successful implementation of early mobilization after cesarean delivery.